Case reportSpecific skin manifestation of B-cell chronic lymphocytic leukaemia - Chodorowska, Grażyna; Szponar, Anna; Gerkowicz, Agnieszka; Juszkiewicz-Borowiec, Maria; Podhorecka, Monika (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
B-cell chronic lymphocytic leukaemia (B-CLL) is the most common type of leukaemia. Besides systemic symptoms, patients may present various forms of skin manifestation. Considering the variety of cutaneous symptomatology, skin lesions in B-CLL patients are divided into specific and non-specific, based on the presence or absence of leukaemic infiltration in the skin. Nowadays it is thought that post-zoster lymphoproliferative skin changes in CLL patients might be a specific cutaneous manifestation of chronic lymphocytic leukaemia. This paper presents a case of a 71-year old male patient with B-cell chronic lymphocytic leukaemia. The patient’s chemotherapy regimen was discontinued due to haemorrhagic zoster followed by dorsal skin ulcers. The patient was admitted to the Dermatological Department and a skin biopsy was performed, which revealed the leukaemic infiltration. Viral aetiology of the ulcers was excluded. The patient was thus re-qualified for chemotherapy. Patients with chronic lymphocytic leukaemia are more prone to numerous infections of various aetiology. It is worth considering that the skin ulcers may be regarded as a complication of these infections, as well as may be a specific cutaneous manifestation of the leukaemia.